ANALISIS PENGARUH PAD, DBH, DAU, DAK DAN PERTUMBUHAN EKONOMI TERHADAP BELANJA MODAL KABUPATEN NGAWI TAHUN 2003-2015 - M. Agus Sudrajat; Irma Diastuti Purniawati (INVENTORY: JURNAL AKUNTANSI, 2017)
The purpose of this study was to determine whether there is Influence Of Local Own Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Economic Growth of the Capital Expenditure The District Ngawi Year 2003-2014 either partial or simultaneously. The population in this study is Ngawi government. This study uses secondary data in the form of budget realization report a Ngawi government in 2003-2014. Testing the hypothesis in this study using multiple linear regression t test, F test and the coefficient of determination. The results of this study concluded that partial variable PAD, DBH, DAU and Economic Growth influence significantly to capital expenditure. While DAK did not significantly influence capital expenditure. Simultaneously variabel PAD, DBH, DAU, DAK and Economic Growth significant effect on capital expenditure. For local government are espected to pay more attention to the proportion of DAK is allocated to capital expenditure.Keywords : Local Own Revenue, Revenue Sharing Fund, General Allocation Fund, Special Allocation Fund, Economic Growth, Capital Expenditure.